A non-transgenic mouse model (icv-STZ mouse) of Alzheimer’s disease: Similarities to and differences from the transgenic model (3xTg-AD mouse) - Chen, Yanxing (2012)
Alzheimer’s disease (AD) can be divided into sporadic AD (SAD) and familial AD (FAD). Most AD cases are sporadic and result from multiple etiologic factors, including environmental, genetic and metabolic factors, whereas FAD is caused by mutations in the presenilins or amyloid-β (Aβ) precursor protein (APP) genes. A commonly used animal model for AD is the 3xTg-AD transgenic mouse model, which harbors mutated presenilin 1, APP and tau genes and thus represents a model of FAD. There is an unmet need to in the field to characterize animal models representing different AD mechanisms, so that potential drugs for SAD can be evaluated preclinically in these animal models. A mouse model generated by intracerebroventricular (icv) administration of streptozocin (STZ), the icv-STZ mouse, shows many aspects of SAD. In this study, we compared the non-cognitive and cognitive behaviors as well as biochemical and immunohistochemical alterations between the icv-STZ mouse and the 3xTg-AD mouse. We found that both mouse models showed increased exploratory activity as well as impaired learning and spatial memory. Both models also demonstrated neuroinflammation, altered synaptic proteins and insulin/IGF-1 (insulin-like growth factor-1) signaling, and increased hyperphosphorylated tau in the brain. The most prominent brain abnormality in the icv-STZ mouse was neuroinflammation, and in the 3xTg-AD mouse it was elevation of hyperphosphorylated tau. These observations demonstrate the behavioral and neuropathological similarities and differences between the icv-STZ mouse and the 3xTg-AD mouse models and will help guide future studies using these two mouse models for the development of AD drugs.